2017
DOI: 10.1038/srep41030
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic ammonia removal and current efficiency by a vermiculite-packed electrochemical reactor

Abstract: The ammonia removal as well as the current efficiency during electrolysis was investigated by using a vermiculite-packed electrochemical reactor under continuous mode. Experimental results showed that adsorption of ammonia by vermiculite and electrolytic desorption of ammonia simultaneously existed in the reactor, leading to 89% removal of initial 30 mg N/L ammonia and current efficiency of 25% under the condition of 2.0 A, 6.0 min hydraulic retention time with 300 mg Cl/L chloride as the catalyst. The ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…5b). The suspected cause for this decreased effluent free chlorine with the presence of fertilizer is due to the consumption by ammonium and transformations to other nitrogenous species due to direct oxidation by the anode and indirect oxidation from free chlorine 6366 . Chlorine is known to react with various organic and inorganic components in water, such as microorganisms but also including ammonium and ferrous iron 1,37,67 .…”
Section: Resultsmentioning
confidence: 99%
“…5b). The suspected cause for this decreased effluent free chlorine with the presence of fertilizer is due to the consumption by ammonium and transformations to other nitrogenous species due to direct oxidation by the anode and indirect oxidation from free chlorine 6366 . Chlorine is known to react with various organic and inorganic components in water, such as microorganisms but also including ammonium and ferrous iron 1,37,67 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Ding et al [ 31 ] removed 90% of ammonia using Ti/RuO 2 -Pt electrodes by the EO method. Similarly, Li et al [ 23 ] reported an 89% ammonia removal at an initial concentration of 30 mg/L using a vermiculite-packed electrochemical reactor. Overall, the ammonia elimination efficiency in the current study was similar to those in previous studies.…”
Section: Resultsmentioning
confidence: 94%
“…We selected the initial concentrations of pollutants based on preliminary experiments and a literature review. For example, Li et al [ 23 ] used 25 mg/L as the initial ammonia concentration during the application of an electrochemical ion-exchange reactor for ammonia removal, while Peings et al [ 24 ] used 30 mg/L as the initial phenol concentration for the removal from an aqueous solution by advance oxidation.…”
Section: Methodsmentioning
confidence: 99%
“…The use of NH 4 Cl as a leaching agent, for one function, provided chloride ions; another crucial role in the electrolytic process was to inhibit the evolution of chlorine gas on the anode, furthermore to avoid the formation of lead dioxide in the anodic oxidation. The following reactions would occur during electrolysis , normalc athode : 0.25em PbCl 4 2 + 2 normale = Pb + 4 Cl normala node : 0.25em 2 Cl 2 normale = Cl 2 4 Cl 2 + 2 NH 4 + = N 2 + 8 H + + 8 Cl …”
Section: Experimental Sectionmentioning
confidence: 99%